2019
DOI: 10.2136/vzj2019.01.0004
|View full text |Cite
|
Sign up to set email alerts
|

Metals and Metalloid Removal by Colloidal Humic Acid–Goethite: Column Experiments and Geochemical Modeling

Abstract: Core Ideas Humic‐acid‐coated goethite effectively removes cationic metals and As(V) from water. Among five elements, sorption of As(V), Cu, and Zn is favored with higher selectivity. In cation–oxyanion binary systems, As(V) enhanced Zn sorption (synergism). Metals less strongly sorbed are desorbed in mixed contamination due to competition for sorption sites. Multi‐surface complexation model in PHREEQC described As(V), Cu, Cd, Ni, and Zn BTCs. Reactive barriers are proposed to scavenge groundwater contaminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…However, the adsorption capacity was lower compared to the batch incubations. The observations are in agreement with those of ( Montalvo and Smolders, 2019 ; Montalvo et al, 2018 ), who also observed that the adsorption capacities in flow-through systems are lower than in batch systems. A likely explanation for this phenomenon is the contact time of the fluid passing through the column as compared to the reaction time of the adsorption process.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the adsorption capacity was lower compared to the batch incubations. The observations are in agreement with those of ( Montalvo and Smolders, 2019 ; Montalvo et al, 2018 ), who also observed that the adsorption capacities in flow-through systems are lower than in batch systems. A likely explanation for this phenomenon is the contact time of the fluid passing through the column as compared to the reaction time of the adsorption process.…”
Section: Discussionsupporting
confidence: 91%
“…The pH of the groundwater in the injection zone and downstream was increased to 9.1 during the injection, and decreased with time until the end of the monitoring period. This increase in pH is assumed to significantly enhance adsorption of zinc onto Goethite particles as reported previously ( Mohammadian et al, 2021 ; Montalvo and Smolders, 2019 ; Montalvo et al, 2018 ). The amount of Goethite nanoparticles injected in the pilot was calculated for an active adsorption barrier over ca.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Soil organic matter is a chemically complex, heterogeneous mixture of thousands of biotically and abiotically processed molecules, and this complexity has led to the use of different approaches for studying its reactions in soils. A predominant approach to reducing the complexity has been through the use of an operationally defined, alkaline extraction to isolate SOM on a pH solubility basis into humic and fulvic acids to represent natural organic matter in chemical studies (Hiemstra et al, 2013; Montalvo and Smolders, 2019). These humic and fulvic acids are thought to be primarily high‐molecular‐weight aromatic molecules formed through polyphenol polymerization reactions (Stevenson, 1994; Sparks, 2003) that occur in natural ecosystems.…”
mentioning
confidence: 99%